Guest

(Cosec theta-sin theta) (sec theta-cos theta)=1/tan theta plus cot theta

(Cosec theta-sin theta) (sec theta-cos theta)=1/tan theta plus cot theta

Grade:10

1 Answers

Arun
25758 Points
4 years ago
Dear student
 
(1/ sin theta   – sin theta) (1/cos theta   – cos theta )
 = (1 – sin2theta) (1 –cos2theta) /sin theta * cos theta
 = sin2 theta *  cos2theta / sin theta * cos theta
 = sin theta * cos theta
 
 
I think you have typed a wrong question.
 
Regards
Arun (askIITians forum expert) 

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free